Accordion training in music schools in Serb academically popular type - Оlena Ustymenko-Kosorich (Academy of Cognitive and Natural Sciences, 2015)
Ustymenko-Kosorich O. А. Accordion training in music schools in Serb academically popular type. The article analyzes the training of accordion Serbian school of academically popular type of two educational areas - professional / amateur, which represent progressive educational system that implements a dual bi-functional program - education of a competent specialist of national public purpose (amateur) and a potential artist of «high art» «means a compilation of genre».